PERAN PUSPAGA SEBAGAI PROGRAM PELAYANAN MASYARAKAT UNTUK MENEKAN ANGKA PERCERAIAN - linda melinda; Usep Saepullah (Sekolah Tinggi Ilmu Syariah Darul Falah Bondowoso, 2024)
This article aims to determine the role of Puspaga as a community service program to reduce the divorce rate, considering that divorce cases in Indonesia are considered to be very high, even though Indonesia is a Muslim-majority country which should avoid factors that can cause divorce. The research method used is analytical descriptive qualitative research, the data collection in this research is library research by collecting articles and previous research results that support the research theme, including divorce cases in Indonesia, how to avoid the factors that cause divorce, as well as information about Puspaga. The research results show that the role of puspaga has been proven to be able to reduce the divorce rate, such as in the Bandung City area, although not directly but through services such as consultations on family problems, pre-marital counseling services and others, resulting in a decrease in the divorce rate in 2023. to 5,861 cases, previously in 2022 there were 7,365 cases. Keywords: Puspaga, Community Service Program, Reducing Divorce Rates